Modulating absorption and charge transfer in bodipy-carbazole donor–acceptor dyads through molecular design. Issue 23 (22nd May 2019) - Strahan, John; Popere, Bhooshan C.; Khomein, Piyachai; Pointer, Craig A.; Martin, Shea M.; Oldacre, Amanda N.; Thayumanavan, S.; Young, Elizabeth R.
Abstract : Bodipy-based donor–acceptor dyads were evaluated using transient absorption spectroscopy to reveal the influence of beta vs . meso substitution on excited-state dynamics. Abstract : Three bodipy-based (BDP = 4, 4-difluoro-4-bora-3a, 4a-diaza- s -indacene) donor–acceptor dyads were designed and synthesized, and their ground-state and photophysical properties were systematically characterized. The electronic coupling between the BDP chromophore and an electron-donating carbazole (Carb) moiety was tuned by attachment via the meso and the beta positions on the BDP core, and through the use of various chemical linkers (phenyl and alkynyl) to afford meso BDP-Carb, meso BDP- phen -Carb, and beta BDP- alk -Carb. meso -Substituted dyads were found to retain ground-state absorption features of the unsubstituted BDP. However, variation of the linkage between the donor and acceptor moieties modulated the photophysical behavior of excited-state deactivation by controlling the rate of photoinduced internal charge transfer (ICT). The beta -substituted dyad dramatically tuned (red shifted) the absorption spectrum, while retaining desired features of the BDP, specifically stability and high extinction coefficients, however the ICT kinetics were accelerated compared to the meso -substituted dyads. Density functional theory (DFT) and time-dependent DFT (TDDFT) were carried out on the six potential dyads formed between BDP and Carb (attachment using the beta and meso positions for all three connections: direct, phenyl and alkynyl) to support the experimental observations. DFT and TDDFT showed molecular orbital density spread across the HOMO level only when attachment occurred through the beta position of BDP. In the meso -substituted BDP-Carb dyads, the molecular orbitals resembled those of the unsubstituted BDP. This work reveals several possible synthetic paradigms to tune photophysical properties with directed synthetic modifications and provides a mechanistic understanding of the ground- and excited- state behavior in these small-molecule donor–acceptor dyads.